TRILATERAL COOPERATION ARRANGEMENT AS THE INDONESIAN DEFENSE STRATEGY TO COUNTER ASYMMETRIC THREATS IN SOUTHEAST ASIA - Luh Putu Ika Primayanti; Tri Legionosuko; Surryanto Djoko Waluyo (Jurnal Pertahanan & Bela Negara, 2020)
The development of the strategic environment has an impact on the rapid development of asymmetrical threats. The Southeast Asian region is one that faces this threat. Indonesia, as one of the countries in the Southeast Asian Region, has conducted a Trilateral Cooperation Arrangement to prevent the asymmetrical threat, especially in the Sulu Sea. This study aims to analyze the Trilateral Cooperation Arrangement strategy as Indonesia's defense strategy in overcoming asymmetrical threats in the Southeast Asian Region. The research method used is a qualitative research method with a phenomenological approach. This study uses the theory of defense science, the concept of strategy, counter terrorism, asymmetric warfare, defense cooperation, cooperative security, and deterrence theory. The results of this study can be divided into three namely, first, the asymmetrical threat that occurs in Southeast Asia, especially the Sulu Sea continues to grow and specifically divided into terrorism; transnational crime namely armed piracy and kidnapping for ransom; and illegal migration. Second, in its implementation, the Trilateral Cooperation Arrangement (TCA) in the Sulu Sea consists of Coordinated Sea Patrol, Air Patrol, Information and Intelligent Sharing and Land Exercise. The four patrols are strategic cooperation which constitutes a unity so that they cannot be separated in parts or functions. However, in its implementation, there are opportunities and challenges that need to be a concern of both policy makers or operational parties. Third, the Trilateral Cooperation Arrangement is a strategy that can overcome the asymmetrical threats that have occurred in Southeast Asia, especially in the Sulu Sea since 2016-2018, but in 2019 the asymmetrical threats in the Sulu Sea have increased. The strategy used is to use defense cooperation as well as using soft power and hard power which provide deterrence effects for asymmetric threat actors. In addition, it strengthens the collaboration of Ministries and Institutions as policy makers, as well as the military army and local governments as operational implementers and supporting rules such as operational procedure rules.Keywords: Asymmetric threats, strategy, Trilateral Cooperation Arrangement (TCA)